Legal, Organizational and Methodological Challenges of Providing Forensic Support for Intellectual Property Protection - E. R. Rossinskaya (Теория и практика судебной экспертизы)
When examining legal, organizational and methodological issues of forensic expertise for the protection of intellectual property the most common forensic examinations are authorship investigation, computer forensic examination, phonoscopic, linguistic, engineering, patent examinations as well as examination of documents. Comparative analysis of the procedural status of an expert in various types of process and in the federal law “On State Forensic Expert Activities in the Russian Federation” is given. Specialist’s procedural position and the evidentiary value of the results of his participation in various types of proceedings in the cases of this category are analysed. Attention is paid to organizational and legal issues of conducting forensic examinations in non-state expert organizations. Based on the analysis of an array of expert opinions, specialists’ opinions and advice on issues related to intellectual property performed in more than 50 nongovernmental organizations positioning themselves as forensic and on monitoring of the websites of these organizations on the Internet, it has been established that the quality of opinions and consultations has little to do with the information provided on the sites. Scientists and specialists for whom forensic expert activity is not the primary one are often involved in conducting forensic examinations in these organizations. They do not know the basics of substantive and procedural law; they do not always realize the legal consequences of their opinions for the participants in court proceedings and exceed their competence. In context of a specific example typical mistakes in cases related to the protection of intellectual property often made by non-state experts are shown. Although the legislator declares the unity of the scientific and methodological approach to expert practice, professional training and the specialization of experts, these requirements often are not met. There is no unity of forensic expert techniques developed in different departments. For other participants in legal proceedings these techniques are practically inaccessible and their testing and implementation are still not often done at the interdepartmental level. The importance of the activities of the Technical Committee for Standardization TC 134 “Forensic examination” is emphasized.